Enzymatic biochemical parameters (ALT, AST, ALP, γ-GT, LDH) in children with acute lymphoblastic leukemia before antineoplastic treatment - Moya S., Jeél (2015)
Objective: To determine the enzymatic biochemical parameters (glutamic pyruvic transaminase (ALT), glutamic oxaloacetic transaminase (AST), alkaline phosphatase (ALP), gamma glutamyltransferase (y-GT), and lactate dehydrogenase (LDH)) in children with acute lymphoblastic leukemia (ALL) before cancer treatment. Material and Methods: A prospective experimental, observational, cross-sectional study was conducted in 30 children between 2 and 15 years old, from several Neoplastic Centers in Lima. Blood collection was performed in BD red cap Vacutainer tubes, processed in the semi-automated analyzer BIOTEC® EMP-168, with Wiener Lab Group enzyme reagents under the modified method Szaaz and UV-Optimized by IFCC, SSCC and SFBC. Finally, coding and tabulation was performed. Results: 60% were boys and 46.7% are between the ages of 2-6 years. Serum levels of AST were increased by 33.3% in boys and 50% in girls. Serum ALT values were increased in 33.3% of boys and 41.7% of girls; only 25% of girls showed increased levels of y-GT values; ALP was increased in 44.4% of boys and 66.7% of girls. Moreover LDH levels were increased in 55.6% of boys and 41.7% of girls. Conclusion: The enzymatic tests LDH, AST, ALT and ALP are increased in children with ALL compared to normal values due to tumor lysis syndrome characterized by electrolyte abnormalities, and as a result of the massive destruction of tumor cells and rapid release of large amounts of intracellular elements.